2020
DOI: 10.1007/s13755-020-00121-9
|View full text |Cite
|
Sign up to set email alerts
|

How can social media analytics assist authorities in pandemic-related policy decisions? Insights from Australian states and territories

Abstract: Background and objectives: Due to COVID-19, various countries introduced lockdowns and limited citizen movements. These restrictions triggered an increased use of digital technologies and platforms by the public. This provides an opportunity for the authorities to capture public perceptions on COVID-19 from social media channels to make informed decisions. The use of social media analytics during pandemics for decision-making, however, is an understudied area of research. Thus, this study aims to generate insi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…While our study was focused on investigating the unique impact of multiple pandemic restrictions on changes in public opinion over time, which has not been examined in prior literature, we found that the association between new COVID-19 case counts and collective attention-one of our ancillary findings-was consistent with prior studies, including the impact of new daily cases on Australian tweets [11] as well as the impact of daily COVID-19 incidence on Reddit posts and comments across the United Kingdom, the United States, Canada, and Italy [12].…”
Section: Comparison With Prior Literaturesupporting
confidence: 81%
See 1 more Smart Citation
“…While our study was focused on investigating the unique impact of multiple pandemic restrictions on changes in public opinion over time, which has not been examined in prior literature, we found that the association between new COVID-19 case counts and collective attention-one of our ancillary findings-was consistent with prior studies, including the impact of new daily cases on Australian tweets [11] as well as the impact of daily COVID-19 incidence on Reddit posts and comments across the United Kingdom, the United States, Canada, and Italy [12].…”
Section: Comparison With Prior Literaturesupporting
confidence: 81%
“…The frequency of tweets about COVID-19-related topics has also been used to measure perceived susceptibility and severity of COVID-19 and was correlated with interventions, public events, and case counts [10]. Another descriptive study of COVID-19-related tweets from Australian states and territories detailed changes in aggregate sentiment trends in relation to COVID-19-related deaths and major COVID-19-related policy events [11] (eg, blocking arrivals from specific countries, expansion of testing criteria, and limits on outdoor gatherings). However, due to the lack of multivariate statistical modeling in the studies listed above, it was not possible to disentangle the independent contribution of these events on tweet frequency or aggregate sentiment and to investigate their relative importance in the shaping of public opinion.…”
Section: Prior Relevant Studiesmentioning
confidence: 99%
“…93 In Australia, Yigitcanlar and colleagues analysed 96 666 tweets and identified that the public's attitude could be captured efficiently through social media analytics. 94 One qualitative content analysis of 30 profiles from Instagram, Twitter, and TikTok in Brunei identified five types of attitudes towards physical distancing: fear, responsibility, annoyance, fun, and resistance. 80 In Turkey, to show the effects of social media on human psychology and behaviour, Arpaci and colleagues 52 used evolutionary clustering analysis on 43 million tweets between March 22 and March 30, 2020.…”
Section: Social Media For Surveillance and Monitoringmentioning
confidence: 99%
“…Twitter allows users to post short text messages called tweets. A massive amount of real-time data is posted by millions of users on various topics including transportation and real-time road traffic [ 4 , 6 , 7 , 8 ]. In the recent decade, the use of Twitter and other social media by researchers and practitioners to study different issues in many application domains and sectors has steadily increased [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%